Photonic and or gate by using fiber coupler - M. Roslan, Sufi (2015)
The development of optical logic gate by using fiber coupler can be realized by properly determine the delay in Pulse Position Propagation (PPM) to set a logic bit in Time Domain Multiplexing (TDM) systems. Soliton has been used to maintain the pulse shape for a long haul distance connection up to 100km. In this study, a numerical modeling of secant hyperbolic soliton pulse based on Nonlinear Schrodinger Equation (NLSE) was performed in balance of Self-Phase modulation and Group velocity dispersion by normalized distance, time and field calculated by 1032 iteration step. Two picosecond soliton pulse transmission in anomalous dispersion region served as input generated inside fiber coupler and the code generator will encode signal within the altered time difference of ±0.25t. The signal would move in the fiber coupler and the phase modulator controls the phase of the bisoliton generation from 0 to 2p. The result is the formation of optical logic AND and OR gate at the phase difference of 0.4p and 1.1p with normalized power of ~6 and parameter offset ε=0.25.